Stress reactivity to an electronic version of the Trier Social Stress Test: a pilot study - Hawn, Sage E.; Paul, Lisa; Thomas, Suzanne; Miller, Stephanie; Amstadter, Ananda B. (Frontiers in Psychology, 2015)
Social stressors that rely on the inclusion of confederates (i.e., Trier Social Stress Test; TSST) are often used in clinical laboratory research paradigms to elicit a measurable stress response in participants. Although effective, the TSST is labor intensive and may introduce error variance as a function of confederate race, gender, and/or response characteristics. The present study aimed to develop and validate an electronic version of the TSST (e-TSST). The primary aim was to compare the e-TSST to an e-neutral control condition; the exploratory aim was to compare the magnitude of stress response elicited by the e-TSST to that elicited by the traditional TSST. Forty-three healthy adults were randomized to the e-TSST or e-neutral condition. Subjective (participant-rated distress) and objective (cortisol, heart rate and blood pressure) indices of stress were collected prior to, and multiple times following, the stressor. Using archival data collected from 19 healthy participants exposed to the traditional TSST in a prior study, stress reactivity was compared between the electronic and traditional versions of the TSST. The e-TSST elicited significant increases in all measures of stress reactivity compared to the e-neutral condition, with the exception of heart rate (HR). Results showed that the magnitude of subjective distress, BP, and HR responses elicited by the e-TSST did not differ significantly from that elicited by the traditional TSST. The traditional TSST elicited significantly higher cortisol than the e-TSST. Although these findings provide initial support for the development of electronic versions of the TSST, further refinement of the e-TSST is warranted prior to broad adoption of this technology. A refined, reliable e-TSST could allow for increased utilization of the TSST by enhancing convenience, reducing labor costs, and limiting potential error variance introduced by human confederates.